Genomic Diversity of Haemophilus influenzae Serotype a in an Outbreak Community—Alaska, 2018. (16th July 2021) - Nolen, Leisha D; DeByle, Carolynn; Topaz, Nadav; Simons, Brenna C; Tiffany, Amanda; Reasonover, Alisa; Castrodale, Louisa; McLaughlin, Joseph; Klejka, Joe; Wang, Xin; Bruce, Michael
Abstract: Background: Haemophilus influenzae serotype a (Hia) can cause severe invasive disease, especially in young children. In 2018, 4 invasive Hia cases occurred in an Alaska community. We used whole-genome sequencing (WGS) to evaluate the relationship of the bacteria from this community and other Alaska patients with invasive Hia. Methods: All carriage (n = 15) and invasive (n = 4) Hia isolates from the outbreak community, together with 15 nonoutbreak Alaska invasive Hia surveillance isolates from 2018, were tested for antimicrobial susceptibility and characterized using WGS. Results: Phylogenetic analysis of both invasive and carriage Hia isolates revealed 2 major clades that differed by an average of 300 core single-nucleotide polymorphisms (SNPs). All isolates from the outbreak community were clustered in 1 subclade, within a larger clade containing 3 nonoutbreak invasive Hia isolates. Comparative genomics did not reveal any genetic mutations that distinguished carriage from invasive isolates. Three (20%) community isolates were rifampin resistant and had a previously unreported mutation in the rpoB gene. Conclusions: In the outbreak community, Hia isolates from carriers were indistinguishable from the invasive Hia isolates. Overall, invasive Hia isolates from Alaska in 2018 were genetically similar. The rifampin resistance mutation is concerning as rifampin is the first-line medication for Hia prophylaxis. Abstract : Haemophilus influenzae serotype a (Hia) isolates from cases and carriers in an outbreak community were not genetically distinguishable. The community isolates were very similar to Hia collected across the state in the same year. Three rifampin-resistant isolates were identified.